Development and Evaluation of a Spot Sensor Glove for the Tactile Prosthetic Hand - Najeh Nemah, Mohammed; Yee Low, Cheng; Ong, Pauline; Ayuni Che Zakaria, Noor (International Journal of Engineering and Technology, 2018)
A tactile glove sensory system of the haptic feedback stimulation system for the upper limb prostheses was developed in this work to enable the patients of the upper limb amputation to recover the sense of touch and slippage. The system features six of a spot piezoresistive force sensors of type Quantum tunnelling composites (QTC) with 10 mm diameter, in order to measure the contact pressure between the hand and the objects. Five sensors were distributed on each fingertip and an extra sensor was mounted on the hand’s palm to cover all the critical point and increase the probability of detecting the contact pressure. The tactile glove was fabricated from the plastic glove equipping with a rigid foundation under each pressure sensor. The computer system was programmed to select the instant greatest signal from the six sensors’ signals; in order to create a critical output signal that can be provided to the haptic feedback stimulator. The touch and the slippage detection experimental tests have been done to examine the functionality of the tactile sensory glove for detecting the touch, start of touch, end of touch grasp, and slippage. The testing results showed that the amputees were able to recover the sensation of the contact pressure using a spot sensor tactile glove developed in this work.